Diagnostic dilemma between medication-related osteonecrosis and oral squamous cell carcinoma in a mandibular lytic lesion. Issue 9 (November 2017) - Tocaciu, S.; Breik, O.; Lim, B.; Angel, C.; Rutherford, N.
Abstract: Osteolytic lesions of the mandible are common, and there are two important differential diagnoses that must be considered: medication-related osteonecrosis of the jaws (MRONJ) and squamous cell carcinoma (SCC). In patients with a history of taking antiresorptive medication as well as risk factors for neoplasia it can be difficult to differentiate between the two. We describe two cases in both of which a mandibular osteolytic lesion was inadequately identified as either MRONJ or SCC because of confusing clinical and histopathological features. We also reviewed relevant publications to identify similar cases. Here we discuss our clinical dilemma when faced with two different conditions that present with similar clinical and histopathological features.